Existence and uniqueness of positive solutions for first-order nonlinear Liouville-Caputo fractional differential equations - Haoues Moussa; Ardjouni Abdelouaheb (University Of Eloued جامعة الوادي, 2020)
We study the existence and uniqueness of positive solutions of the rst-order nonlinear Liouville Caputo fractional differential equation ........................................................ ........................................................ where ....... In the process we convert the given fractional differential equation into an equivalent integral equation. Then we construct appropriate mappings and employ the Krasnoselskii xed point theorem and the method of upper and lower solutions to show the existence of a positive solution of this equation. We also use the Banach xed point theorem to show the existence of a unique positive solution.
Intervention
Keywords: Fractional di¤erential equation; Positive solutions; Fixed point theorem; Existence and uniqueness